Information and Quality When Motivation is Intrinsic: Evidence from Surgeon Report Cards - Kolstad, Jonathan T (American Economic Review, 2013)
If profit maximization is the objective of a firm, new information about quality should affect firm behavior only through its effects on market demand. I consider an alternate model in which suppliers are motivated by a desire to perform well in addition to profit. The introduction of quality “report cards” for cardiac surgery in Pennsylvania provides an empirical setting to isolate the relative role of extrinsic and intrinsic incentives in determining surgeon response. Information on performance that was new to surgeons and unrelated to patient demand led to an intrinsic response four times larger than surgeon response to profit incentives. (JEL D83, I11, L15)